A macro view of two decades of violence in America - Joubert, Paul E. (American journal of criminal justice, 1988)
This paper attempts to predict variations in violence at the state level using structural indicators. Multiple regression models were constructed for 1960, 1970, and 1980. Percent Black and Percent Urban were found to be the strongest predictors of violent crime in all three years. Additionally, two longitudinal models for changes in violence from 1960–1970, and from 1970–1980 were constructed. Changes in Per Capita Income and Percent Black were strongest predictors in the 1960–1970 model. From 1970–1980, changes in violence were best predicted by changes in Density Per Square Mile and Per Capita Income.